Desafios da inclusão das pessoas com deficiência no trabalho: contribuições de uma experiência - Navas, Paula Márcia Gomes (2019)
From the twentieth century, both in Brazil and in other countries, legislation is well known, which aims to promote the inclusion of people with disabilities in different social spheres, be they educational, work or leisure. In this way, this research seeks to contribute to the debates about the challenges posed for the participation of persons with disabilities in the world of work, through the understanding that people with disabilities have about this experience considering how they recognize themselves in the world of work and how they identify the meaning of work in their lives. This is a qualitative case study that aims to analyze the work experiences of people with disabilities participating in the ATO Project - Work and Opportunity Action, held in the city of São Carlos - SP. The study was developed in two stages: (i) documentary research in the Project files, such as activity reports and other available records; and (ii) semi-structured interviews with people with disabilities who dealt with their daily lives: a) when they were included by the ATO Project; b) during the phase in which the Project was active; c) after the closing of the Project until the moment of the interview. The information in the reports and records of the Project were presented seeking to build a timeline for the activities, actions and strategies carried out. The interviews were analyzed from the categorical content analysis. According to documentary research, among the 85 people who were included in the work world by the Project, 15 presented interaction profile and interpersonal communication. Through telephone contact and social networks, five of these 15 people agreed to participate in the study. Through a transcription process, interview data were organized into categories, considering the issues that were addressed in the interviews: Life before the ATO Project; The insertion in the Project and its Consequences; Life after the ATO Project. These categories indicated the prevalence of work in the industries of transformation, education, commerce and services, from subjects such as employability restricted to that provided by the Quota Law; the type of function performed in a company in accordance with the constraints; the stereotype in relation to the type of disability; levels of schooling and new job opportunities, influenced by the type of disability; the re-signification of social participation; interpersonal relationships and their development; the execution of the tasks of daily life; the importance of the support network and the quotidian It can be observed that interpersonal relations were promoted or improved with inclusion in the work as well as positive changes, which led the DPs to new positions and protagonism in the family and financial organization, the expansion of their support networks, purchasing power and social participation. Processes of illness, promoted from work, similar to those of other workers have also been identified. The positive results and the limitations and barriers encountered by the DPs enabled recommendations to expand the legal attributions of inclusion programs in the world of work beyond the occupation of vacancies made possible by the Quota Law, emphasizing the need to attend to the complexity of the processes. It is essential that the programs strengthen the study of jobs and people skills and their experiences, as well as the monitoring of the permanence in the work as strategies to enable greater participation in the world of work respecting the right to work as part of the contribution of people to the construction of the world.